An Industrial quality control study on company XYZ - Gonzales, Michelle Lynn (College of Engineering, 2006)
Quality is one of the most important factors to consider in having a successful performance. A good quality system will probably increase the company's credibility, total profit, and most importantly, customer's satisfaction. The objective of this study is to improve the existing quality control and assurance system of Company XYZ that focuses on reducing clients' complaints resulting to product reworks and rejects, with the use of different statistical quality control tools and principles. In documenting the manufacturing process and present quality system of the company, interview with the key workforce, direct observations, and study of the written procedures and historical and present data were done. The Failure Mode, Effect and Criticality Analysis (FMECA) was used in analyzing the potential fail mode or weaknesses of some critical processes and quality characteristics. It was found out that ranks 1-3 of the most critical processes could result to leakages at can parts. The same result appeared after constructing the Pareto Diagram of the data on customer complaints where leaks, followed by rusts and dents are found to have the highest frequencies. The group then constructed the Ishikawa Diagrams of these defects to identify its causes. Stream Diagnostic Charts of the Overall Production (based on the interview with the Quality Control Group Leader) and per plant divisions (based on the interview with division supervisors and machine operators) were also constructed. After thorough brainstorming and analysis, the group decided to propose recommendations that could possibly minimize the existence of problems identified. Among these recommendations are the following: introduction of Statistical Process Control (SPC), strictly implementation of the quality system and procedures, hiring of additional quality control inspectors, and other quality improvement guidelines.